1995
DOI: 10.3758/bf03205464
|View full text |Cite
|
Sign up to set email alerts
|

Repetition blindness under minimum memory load: Effects of spatial and temporal proximity and the encoding effectiveness of the first item

Abstract: Repetition blindness (RB) refers to the reduced performance in reporting a repeated as opposed to a nonrepeated item in rapid serial visual presentation. In Experiment 1, we found RB for two-item stimuli in uncertain locations. The magnitude of RB decreased significantly with increases in interstimulus interval, but not with increases in spatial separation, indicating that RB is determined primarily by temporal factors. In Experiment 2, we found RB when subjects were required to report only the second of two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
132
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(154 citation statements)
references
References 55 publications
17
132
5
Order By: Relevance
“…However, spatial RB is not dependent on these dual-item report requirements, and is robustly observed even when participants only have to report a single item (Luo & Caramazza, 1995). The number of items to report, therefore, does not distinguish the present experiment from RB.…”
Section: Resultsmentioning
confidence: 66%
“…However, spatial RB is not dependent on these dual-item report requirements, and is robustly observed even when participants only have to report a single item (Luo & Caramazza, 1995). The number of items to report, therefore, does not distinguish the present experiment from RB.…”
Section: Resultsmentioning
confidence: 66%
“…However, when error performance on the unrepeated trials is used as a measure to correct the size of RB (Park and Kanwisher, 1994) no significant reduction in the size of the effect has been found. Furthermore, although Fagot and Pashler (1994) failed to find RB in tasks that do not require full report of items, as expected by the hypothesis of retrieval interference, other studies, using a variety of experimental paradigms, have found RB independently of any requirement to overtly report both occurrences of a repeated item (e.g., Kanwisher et al, 1995, Exp.3;Mozer, 1989;Luo and Caramazza, 1995; see also Bjork and Murray, 1977, and Santee and Egeth, 1980.…”
Section: Introductionmentioning
confidence: 67%
“…3). Similarly, Luo and Caramazza (1995) found RB instead of repetition priming when subjects were asked to report only the second occurrence of the repeated item. Thus, the type-refractoriness hypothesis remains a viable framework in which to explain the RB phenomenon.…”
Section: Introductionmentioning
confidence: 84%
“…For example, in Kanwisher's (1987) study, in which there were many distractors, only type activation may have occurred for the first occurrence of the repeated item, and as a result, repetition benefited target report. In Luo and Caramazza's (1995) study, however, there were only two items (the subjects having to report only the second stimulus), and therefore, it is possible that the subjects may have completely tokenized the first item, which would have resulted in a repetition deficit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that repetition blindness occurs when memory demands are reduced (Chun, 1997;Dux & Marois, 2007;Luo & Caramazza, 1995 and even when no recall is required (Hochhaus & Johnston, 1996;Johnston et al, 2002). Thus, although retrieval failure contributes to some effects of repetition seen in RSVP streams, it is not responsible for all of them.…”
Section: Implications For Theories Of Repetition Blindnessmentioning
confidence: 99%